Current state and prospects of instruments of monetary policy management in Kazakhstan (Journal of Economic Research & Business Administration, 2017)
The article examines the current instruments and tools of monetary policy in Kazakhstan. The relevance of the article is the main prerequisite for the sustainable economic development of any country, which is the formation of a clear mechanism for regulating monetary-credit policy. The growing importance of Kazakhstan’s monetary policy in the modern market economy is provided by the growth and development of economic management methods and the transition to sustainable economic growth. Nevertheless, the effectiveness of this policy is still far from high. The main goal of the article is to improve the instruments for managing the monetary and credit policy of state regulation in the Republic of Kazakhstan, taking into account the current situation in the world economy and the national economy. On the basis of the identified goal, the issues of improving the management tools of the monetary policy of state regulation, the specifics of the implementation of the state monetary policy, the analysis of modern monetary policy instruments in Kazakhstan were considered. The instruments of the monetary and credit policy of state regulation, the main problems in the current situation and the ways of their solution, including the features of implementing the important instruments of monetary policy.